Haemoparasites of village goats in southwest Nigeria - Opasina, B.A. (1987)
Assesses the levels of prevalence of blood parasites among village goats over 12 months in 4 groups of villages in Southwest Nigeria, w. particular emphasis on the very high infection rate from Trypanosoma vivax and Babesia motasi.